Վարդան Մամիկոնեանի «կարմիր» մականուան շուրջ - Խորիկեան, Յովհաննէս (տպ. Atlas)
According to the viewpoint of some specialized literature, Vardan Mamikonyan was the king in the Battle of Avarayr in 451. We have made an attempt to confirm this view. In our opinion Vardan Mamikonyan’s nickname ‘Red’ has a specific meaning. In the case of Vardan Mamikonyan it would be very simple to connect the origin of the nickname ‘Red’ to the red color that has a Christological meaning since in the Battle of Avarayr everyone was martyred in the holy blood of martyrdom. In fact, the honorary name of Vardan Mamikonyan had a different meaning at first. Later on, our church historians connected the ‘Red’ nickname with martyrdom and Vardan Mamikonyan was called a Saint, and Blissful as well. With reference to our research, red clothing was a symbol of royal power from ancient times, and Vardan Mamikonyan wore red royal clothing. For this very reason he was given the nickname ‘Red’. Since then the Armenian church has associated ‘Red’ with the blood of those martyred for the sake of the Christian faith.
Keywords: Հայոց պատմութիւն; Մականուններ; Վարդան Մամիկոնեան